IMPLEMENTASI PEMBELAJARAN STEM TERINTEGRASI MELALUI DEMONSTRASI TEKNOLOGI, SIMULASI DESMOS, DAN PRAKTIK ENGINEERING PADA SISWA SMA - Stevanus Trionanda; Elisa Mayang Sari; Ilham Nur Dimas Yahya; Subkhan; Charlotha; Michael Salim Wijaya (Universitas Nias Raya, 2026)
The development of technology and the demand of 21-st century skills encourage the need for STEM (Science, Technology, Engineering, and Mathematics) learning in order to develop students’ conceptual understanding, learning motivation, and critical thinking. However, the implementation of STEM learning in schools face problems such as limited integrated, interactive and practice-based learning activities. Therefore, this community service was carried out to give STEM learning through science material provision, technology demonstrations, mathematical simulations using the Desmos application, and simple engineering practices to Harapan High School students in Sungailiat. The activity was held using practice method, demonstration, hands-on practice, and mentoring involving 19 grade 10 students. Evaluation was conducted using questionnaires on understanding, learning motivation, and participant satisfaction which were then analyzed through Method of Successive Interval (MSI) conversion, validity test, reliability test, and Wilcoxon test. Furthermore, based the Wilcoxon test results showed a p value < 0.05 for all indicators, which indicates a increase on students’ conceptual understanding of STEM and learning motivation after participating in the program. Thus, this community service activity has successfully provided an interactive and applicable learning experience, and has the potential to become a STEM learning model that can be developed sustainably in schools.